2014
DOI: 10.1021/nl500277c
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mapping and Quantification of Soft and Hard Protein Coronas at Silver Nanocubes

Abstract: Protein coronas around silver nanocubes were quantified in serum-containing media using localized surface plasmon resonances. Both soft and hard coronas showed exposure-time and concentration-dependent changes in protein surface density with time-dependent hardening. We observed spatially dependent kinetics of the corona-formation at cube edges/corners versus facets at short incubation times, where the polymer stabilization agent delayed corona hardening. The soft corona contained more protein than the hard co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 40 publications
3
65
0
2
Order By: Relevance
“…[36][37][38] Recently, protein coronas adsorbed on polyvinylpyrrolidone-stabilized silver nanocubes in fetal bovine serum (FBS)-containing media were also quantified, using localized surface plasmon resonances. 32 The soft corona formation was identified at the cube edges/corners versus facets at short incubation times. 32 The soft corona also contained more proteins than the hard corona at all points (eightfold difference in 10% serum condition; Figure 6).…”
Section: Protein Adsorption On Various Npsmentioning
confidence: 97%
See 3 more Smart Citations
“…[36][37][38] Recently, protein coronas adsorbed on polyvinylpyrrolidone-stabilized silver nanocubes in fetal bovine serum (FBS)-containing media were also quantified, using localized surface plasmon resonances. 32 The soft corona formation was identified at the cube edges/corners versus facets at short incubation times. 32 The soft corona also contained more proteins than the hard corona at all points (eightfold difference in 10% serum condition; Figure 6).…”
Section: Protein Adsorption On Various Npsmentioning
confidence: 97%
“…32 The soft corona formation was identified at the cube edges/corners versus facets at short incubation times. 32 The soft corona also contained more proteins than the hard corona at all points (eightfold difference in 10% serum condition; Figure 6). 32 This study suggests that polymer-coated NP coating may influence the kinetics of corona formation or protein distribution on NPs in biological media.…”
Section: Protein Adsorption On Various Npsmentioning
confidence: 97%
See 2 more Smart Citations
“…1B), indicating that AgNPs were well dispersed in culture medium. The slight increase of hydrodynamic size should be due to the formation of protein corona on AgNPs [39,40]. The zeta-potential analysis showed that AgNPs were negatively charged in culture medium over the time course (Fig.…”
Section: Screening Of Sublethal Concentrations Of Agnps In Mel Cellsmentioning
confidence: 96%